The programme of Zeno of Elea’s philosophy - Olesiński, Dariusz (Folia Philosophica, 2000)
The aim of the present article is a reconstruction of Zeno of Elea’s philosophical programme, based in Plato’s testimony, which is meant to contribute to our better understanding not only of Zeno’s argument, but also of Plato’s Parmenides. The author, owing to his making use of a suggestion contained in the dialogue, is able to collect Zeno’s paradoxes according to one interpretative key, so that they form a succession of coherently combined arguments, each of which refutes one by one the possible ways of understanding plurality. As a result, the traditional distinction into the paradoxes of movement and of plurality is undermined. Moreover, in the light of the interpretation put forward here, some of the attempts to avoid the said paradoxes - particularly the ones proposed by Aristotle - turn out to be inadequate.